Chapter 1 The three faces of accountability - Pasquino, Gianfranco (Taylor & Francis, 2023)
Accountability is not an event, but a process. The purpose of the present chapter is to discuss the three faces or phases of accountability: taking into account, keeping into account and giving an account. In doing so attention is paid to the fact that parties and candidates in the course of one election need to learn and take into account what voters want, that their activities as elected official need to reflect the voters' demands and that they need to go back to the voters to explain what they did when they were in office.